2022
DOI: 10.7150/ijbs.65861
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lung epithelial cell senescence in smoking-induced COPD/emphysema by microR-125a-5p via Sp1 mediation of SIRT1/HIF-1a

Abstract: Chronic obstructive pulmonary disease (COPD) affects the health of more than 300 million people worldwide; at present, there is no effective drug to treat COPD. Smoking is the most important risk factor, but the molecular mechanism by which smoking causes the disease is unclear. The senescence of lung epithelial cells is related to development of COPD. Regulation of miRNAs is the main epigenetic mechanism related to aging. β-Galactose staining showed that the lung tissues of smokers have a higher degree of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Further, HCA and KEGG functional enrichment analysis results demonstrated that ANIT‐induced cholestasis in mice led to a global alteration in hepatic gene expression, possibly mainly related to bile acids metabolic pathways, which was obviously reverted by LQ pretreatment. Among the 94 miRNAs, certain miRNAs, such as miR‐34a (Castro et al, 2013), miR‐155 (Wang et al, 2021), miR‐221 (Peng et al, 2018), and miR‐125a (Wu et al, 2022), participate in regulating the expression of Sirt1, which is involved in the physiological processes of apoptosis, inflammatory response and cell senescence. Besides, our previous study found that miR‐155 functions act as a significant regulatory factor in the Nrf2 signaling pathway (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Further, HCA and KEGG functional enrichment analysis results demonstrated that ANIT‐induced cholestasis in mice led to a global alteration in hepatic gene expression, possibly mainly related to bile acids metabolic pathways, which was obviously reverted by LQ pretreatment. Among the 94 miRNAs, certain miRNAs, such as miR‐34a (Castro et al, 2013), miR‐155 (Wang et al, 2021), miR‐221 (Peng et al, 2018), and miR‐125a (Wu et al, 2022), participate in regulating the expression of Sirt1, which is involved in the physiological processes of apoptosis, inflammatory response and cell senescence. Besides, our previous study found that miR‐155 functions act as a significant regulatory factor in the Nrf2 signaling pathway (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of miRNAs, termed senescence-related miRNAs, can act as senescence inducers. [ 36 ] Philipot et al identified that miR-24 negatively regulates p16 expression and promotes cellular senescence in human chondrocytes. [ 37 ] Afanasyeva et al reported that miR-885-5p exertes antitumor effects by interfering with cell cycle progression and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-199-5p expression was elevated in HPMVECs transfected with miR-34a precursor gene. In a recent study, Wu et al (110) found that miR-125a-5p levels were higher in normal smokers and COPD smokers than in the healthy population. Furthermore, researchers have used smoke to induce COPD in mouse models.…”
Section: Non-coding Rnamentioning
confidence: 94%